Succeed in the toeic test : Self - practice authentic test format, practical usage / Andrew Betsis, Lawrence Mamas ; editor Yuniar Widiastuti , Dwi Wahyu Priyanto, Raymond S...1st - BETSIS, Andrew; Mamas, Lawrence; Yuniar Widiastuti; Dwi Wahyu Priyanto; Raymond S (Erlangga, 2014)
...volume.: ilus.; 26 cm + CD